Answer:
Step-by-step explanation:
It will just be 12, since the uncles can go in one group and fit 12 uncles, and than the aunts can get photographed in 2 groups that add up to 12
Answer:
![\frac{\frac{4}{5}}{\frac{1}{3}+\frac{1}{5}-\frac{3}{5}}=-12](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cfrac%7B4%7D%7B5%7D%7D%7B%5Cfrac%7B1%7D%7B3%7D%2B%5Cfrac%7B1%7D%7B5%7D-%5Cfrac%7B3%7D%7B5%7D%7D%3D-12)
Step-by-step explanation:
Considering the expression
![\frac{\frac{4}{5}}{\frac{1}{3}+\frac{1}{5}-\frac{3}{5}}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cfrac%7B4%7D%7B5%7D%7D%7B%5Cfrac%7B1%7D%7B3%7D%2B%5Cfrac%7B1%7D%7B5%7D-%5Cfrac%7B3%7D%7B5%7D%7D)
Solution Steps:
![\frac{\frac{4}{5}}{\frac{1}{3}+\frac{1}{5}-\frac{3}{5}}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cfrac%7B4%7D%7B5%7D%7D%7B%5Cfrac%7B1%7D%7B3%7D%2B%5Cfrac%7B1%7D%7B5%7D-%5Cfrac%7B3%7D%7B5%7D%7D)
as
![\mathrm{Combine\:the\:fractions\:}\frac{1}{5}-\frac{3}{5}:\quad -\frac{2}{5}](https://tex.z-dn.net/?f=%5Cmathrm%7BCombine%5C%3Athe%5C%3Afractions%5C%3A%7D%5Cfrac%7B1%7D%7B5%7D-%5Cfrac%7B3%7D%7B5%7D%3A%5Cquad%20-%5Cfrac%7B2%7D%7B5%7D)
so
![\mathrm{Apply\:the\:fraction\:rule}:\quad \frac{\frac{b}{c}}{a}=\frac{b}{c\:\cdot \:a}](https://tex.z-dn.net/?f=%5Cmathrm%7BApply%5C%3Athe%5C%3Afraction%5C%3Arule%7D%3A%5Cquad%20%5Cfrac%7B%5Cfrac%7Bb%7D%7Bc%7D%7D%7Ba%7D%3D%5Cfrac%7Bb%7D%7Bc%5C%3A%5Ccdot%20%5C%3Aa%7D)
![=\frac{4}{5\left(\frac{1}{3}-\frac{2}{5}\right)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B4%7D%7B5%5Cleft%28%5Cfrac%7B1%7D%7B3%7D-%5Cfrac%7B2%7D%7B5%7D%5Cright%29%7D)
join ![\frac{1}{3}-\frac{2}{5}:\quad -\frac{1}{15}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D-%5Cfrac%7B2%7D%7B5%7D%3A%5Cquad%20-%5Cfrac%7B1%7D%7B15%7D)
so
![=\frac{4}{5\left(-\frac{1}{15}\right)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B4%7D%7B5%5Cleft%28-%5Cfrac%7B1%7D%7B15%7D%5Cright%29%7D)
![\mathrm{Remove\:parentheses}:\quad \left(-a\right)=-a](https://tex.z-dn.net/?f=%5Cmathrm%7BRemove%5C%3Aparentheses%7D%3A%5Cquad%20%5Cleft%28-a%5Cright%29%3D-a)
![=\frac{4}{-5\cdot \frac{1}{15}}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B4%7D%7B-5%5Ccdot%20%5Cfrac%7B1%7D%7B15%7D%7D)
![\mathrm{Apply\:the\:fraction\:rule}:\quad \frac{a}{-b}=-\frac{a}{b}](https://tex.z-dn.net/?f=%5Cmathrm%7BApply%5C%3Athe%5C%3Afraction%5C%3Arule%7D%3A%5Cquad%20%5Cfrac%7Ba%7D%7B-b%7D%3D-%5Cfrac%7Ba%7D%7Bb%7D)
![=-\frac{4}{5\cdot \frac{1}{15}}](https://tex.z-dn.net/?f=%3D-%5Cfrac%7B4%7D%7B5%5Ccdot%20%5Cfrac%7B1%7D%7B15%7D%7D)
![\mathrm{Multiply\:}5\cdot \frac{1}{15}\::\quad \frac{1}{3}](https://tex.z-dn.net/?f=%5Cmathrm%7BMultiply%5C%3A%7D5%5Ccdot%20%5Cfrac%7B1%7D%7B15%7D%5C%3A%3A%5Cquad%20%5Cfrac%7B1%7D%7B3%7D)
so
![=-\frac{4}{\frac{1}{3}}](https://tex.z-dn.net/?f=%3D-%5Cfrac%7B4%7D%7B%5Cfrac%7B1%7D%7B3%7D%7D)
![\mathrm{Simplify}\:\frac{4}{\frac{1}{3}}:\quad \frac{12}{1}](https://tex.z-dn.net/?f=%5Cmathrm%7BSimplify%7D%5C%3A%5Cfrac%7B4%7D%7B%5Cfrac%7B1%7D%7B3%7D%7D%3A%5Cquad%20%5Cfrac%7B12%7D%7B1%7D)
so
![=-\frac{12}{1}](https://tex.z-dn.net/?f=%3D-%5Cfrac%7B12%7D%7B1%7D)
![\mathrm{Apply\:rule}\:\frac{a}{1}=a](https://tex.z-dn.net/?f=%5Cmathrm%7BApply%5C%3Arule%7D%5C%3A%5Cfrac%7Ba%7D%7B1%7D%3Da)
![=-12](https://tex.z-dn.net/?f=%3D-12)
Therefore
![\frac{\frac{4}{5}}{\frac{1}{3}+\frac{1}{5}-\frac{3}{5}}=-12](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cfrac%7B4%7D%7B5%7D%7D%7B%5Cfrac%7B1%7D%7B3%7D%2B%5Cfrac%7B1%7D%7B5%7D-%5Cfrac%7B3%7D%7B5%7D%7D%3D-12)
Answer:
where is the question
have a good day :)
Step-by-step explanation: